2019
DOI: 10.1111/vox.12756
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic major histocompatibility complex antigens are necessary and sufficient for partial tolerance induced by transfusion of pathogen reduced platelets in mice

Abstract: Background And Objectives Alloimmunization is common following transfusion with platelet-rich plasma (PRP) and can cause complications such as platelet refractoriness or transplant rejection. It has previously been shown that pathogen reduction of PRP with riboflavin and UV light (UV+R) can protect against alloimmunization in mice and induce partial tolerance to subsequent transfusions.Materials and Methods Using B6 H2 d congenic mice, this study evaluated the relative contributions of major histocompatibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Earlier studies have shown that the presence of WBCs significantly increases the allo‐response to PRP transfusion, with optimal protection observed with the use of a combination of leukoreduction and UV + R . Furthermore, we have found that MHC antigens from WBCs are critical for induction of the partially tolerogenic phenotype observed with UV + R treatment . Therefore, WBCs were added back into the leukoreduced PRP in our experimental model to simulate a worst‐case scenario of alloimmunization.…”
Section: Discussionmentioning
confidence: 96%
“…Earlier studies have shown that the presence of WBCs significantly increases the allo‐response to PRP transfusion, with optimal protection observed with the use of a combination of leukoreduction and UV + R . Furthermore, we have found that MHC antigens from WBCs are critical for induction of the partially tolerogenic phenotype observed with UV + R treatment . Therefore, WBCs were added back into the leukoreduced PRP in our experimental model to simulate a worst‐case scenario of alloimmunization.…”
Section: Discussionmentioning
confidence: 96%
“…Adoptive transfer studies were conducted to avoid complications from potent anti-BALB/c antibodies at the time of secondary challenge for the Allo/Allo group, 61 which could mediate removal of the antigen prior to T-cell activation. This also examined whether tolerance seen in the Allo PRT/Allo group was transferable.…”
Section: Adoptive Transfermentioning
confidence: 99%
“…Furthermore, while the effect of PRT or UV light on blood components has been evaluated in vitro, 21,[55][56][57][58][59][60] in vivo studies have focused predominantly on alloantibody outcomes, with little known about cellular responses. 18,21,22,61 Immune tolerance, including induction of T regulatory cells (T reg cells), has been associated with other UV treatment strategies in humans and animal models, [62][63][64][65][66][67][68] suggesting similar mechanisms may be induced by PRT.…”
Section: Introductionmentioning
confidence: 99%
“…18,[22][23][24] Interstrain platelet transfusions in mice have been used to model antibodydependent platelet transfusion refractoriness that develops in multiply transfused human patients, characterize its pathogenesis and examine ways that this complication can be circumvented. [25][26][27][28][29][30] However, many studies have failed to consider the possibility that the immunized mice may have produced both MHC-specific and GPIIb/IIIa-specific alloantibodies. Findings described here and in a previous report 1 show that interstrain AA mismatches in extracellular domains of GPIIb/IIIa are common and highly immunogenic (at least in the mouse strains studied by us) and that antibodies recognizing them are capable of destroying platelets.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior contrasts markedly with experience in humans transfused with whole blood or platelets in whom alloantibodies against platelet‐specific GPs (HPA antibodies) are relatively uncommon 18–21 but who often become immunized against Class I HLA antigens and may become refractory to randomly selected platelet transfusions as a consequence 18,22–24 . Interstrain platelet transfusions in mice have been used to model antibody‐dependent platelet transfusion refractoriness that develops in multiply transfused human patients, characterize its pathogenesis and examine ways that this complication can be circumvented 25–30 . However, many studies have failed to consider the possibility that the immunized mice may have produced both MHC‐specific and GPIIb/IIIa‐specific alloantibodies.…”
Section: Discussionmentioning
confidence: 99%